Hydrodynamic Characteristics and Riverbed Evolution Analysis of the Bazizui Straight Branching Channel in Xinjiang River Based on MIKE21 - HU Kelong; JI Yong; CEN Yixing; ZHONG Heye; ZHANG Yue; ZHANG Lichen; WANG Yin; ZHANG Jie (Renmin Zhujiang)
To clarify the hydrodynamic characteristics and riverbed evolution trend of the branching channel bank in the Bazizui shipping section of Xinjiang River,this paper builds the two-dimensional mathematical model of the research water area by MIKE21 hydrodynamic module.It employs the hydrological data of Meigang Station to calibrate the model and verify the accuracy.On this basis,the hydrodynamic characteristics in different hydrological periods of the straight branching channel of Xinjiang River are analyzed,and the evolution trend of the branching channel section is clarified.The results show that the left branch is the main water branch,and the diversion ratio of the diversion channel decreases with the increase in flow.The velocity of flow is irregularly distributed and varies significantly between regions.The main stream appears in the left branch of the diversion section,and the maximum flow velocity is confirmed in the narrow part.The water level decreases uniformly from the diverging area to the confluence area.The overall stability of river pattern development and evolution is good,and the evolution of the water channel is mainly reflected in the local changes of riverbed scouring and silting in branching channels.The model can effectively simulate the diversion ratio and water level variation of the branching channel,which can provide a scientific basis for the study of river safety protection and navigation stability.